2020
DOI: 10.1111/ajad.13115
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Heroin‐Methamphetamine (Goofball) Use and Related Morbidity Among Seattle Area People Who Inject Drugs

Abstract: Background and Objectives Methamphetamine use is increasing in the United States, potentially including the simultaneous injection of methamphetamine with heroin (goofball). We compared demographic, behavioral, contextual, and health factors among people who inject drugs (PWID) in the Seattle area and who reported that their main drug was goofball, heroin, or methamphetamine. Methods We used data from 2017 and 2019 cross‐sectional surveys of clients at Public Health—Seattle & King County's syringe services pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…Among reproductive age and pregnant women, methamphetamine is one of the most abused substances ( 30 , 31 ). A study based on persons who inject drugs in Seattle found a higher proportion of women co-using heroin and amphetamine instead of using these substances alone ( 32 ). Women with OUD have also been found to have higher rates of treatment attrition in multiple studies ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among reproductive age and pregnant women, methamphetamine is one of the most abused substances ( 30 , 31 ). A study based on persons who inject drugs in Seattle found a higher proportion of women co-using heroin and amphetamine instead of using these substances alone ( 32 ). Women with OUD have also been found to have higher rates of treatment attrition in multiple studies ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing prevalence of concurrent stimulant use, patients with OUD experiencing homelessness may be particularly challenging to engage in OPAT care. Local studies by public health colleagues noted increased use of both heroin and methamphetamine from 2017 to 2019 in people who inject drugs (PWID) in the Seattle area who were also experiencing homelessness [ 8 ]. One review identified a specific need to better understand the effect of combining OPAT with addiction treatment interventions [ 9 ].…”
mentioning
confidence: 99%
“…Seattle has also demonstrated increased use of goofball (heroin + methamphetamine simultaneously). Presumably, this increase has increased the mixing of sexual and needle sharing networks, although self-reported prevalence of HIV was lower among goofball users compared to primary methamphetamine users [ 39 ]. Meacham et al demonstrated an association among PWID who co-injected heroin and methamphetamine and HIV drug injection behaviors as well as sexual risk behavior (sex exchange and drug use before sex) compared to PWID who did not co-inject.…”
Section: Discussionmentioning
confidence: 99%